Gaya Belajar SAVIO: Membentuk Pelajar Multitalent dalam Pembelajaran Bahasa Arab - Junaedi, Achmad; Rozi, Fathor; Rumiyanti, Rumiyanti (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2023)
The purpose of this study is to find out how SAVIO's learning style activities can form multitalented students in learning Arabic for students. This research includes phenomenological research with a qualitative approach. The location of the research was carried out at MI Nahdlatul Ulama' Kraksaan. Data collection techniques were carried out through the process of observation, in-depth interviews, and documentation. The data analysis technique uses the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. The validity of the data with the process of triangulation of sources and techniques. The results of this study state that the SAVIO learning style applied by MI Nahdhatul Ulama', especially in learning Arabic, reaches the stage of forming students who master many fields (multitalent) through four main activities, namely (1) see and demonstrate, (2) matching picture, (3 ) analyze problem solving with true or false, and (4) dialogue habits. So this SAVIO learning style can awaken students' integrated intelligence in full by combining physical movement with intellectual activity, creating a better, interesting and effective learning atmosphere.